2016
DOI: 10.18203/2320-6012.ijrms20160512
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude and practice of Tanta University medical students towards hepatitis B and C

Abstract: Background: Egypt lies among the world's highest prevalence rates of HCV and intermediate levels of HBV infection. The objectives of the study were detection of the knowledge, attitude and practice of Medical Students of Tanta University towards hepatitis B and C. Methods: This was a cross-sectional study, conducted in The Faculty of Medicine, Tanta University, Egypt; from 15th October 2013 to 15th of January 2014. Results: The study included 185 Students; their ages ranged between 17 to 28 years with a mean 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
15
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 7 publications
3
15
5
Order By: Relevance
“…11-13 95% of the respondents were aware about the availability of Hepatitis B vaccine which concurs with the results reported by Hussain FS et al 14 Most of the respondents had adequate knowledge about the modes of transmission which was in line of agreement with the results. 12,15 In contrast to the results of current study, lower knowledge levels. [16][17][18] Lower proportion (45%) of the students knew that living with the Hepatitis B or Hepatitis C patient was not a risk factor which was in contrast to result reported by authors.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…11-13 95% of the respondents were aware about the availability of Hepatitis B vaccine which concurs with the results reported by Hussain FS et al 14 Most of the respondents had adequate knowledge about the modes of transmission which was in line of agreement with the results. 12,15 In contrast to the results of current study, lower knowledge levels. [16][17][18] Lower proportion (45%) of the students knew that living with the Hepatitis B or Hepatitis C patient was not a risk factor which was in contrast to result reported by authors.…”
Section: Discussioncontrasting
confidence: 99%
“…19 Majority (95%) of the respondents in the present study requested for the new blade/ sterilized instruments on a visit to a hair salon while only 79.5% of the respondents elicited this practice. 12 86.43% of the respondents in the current study reported on getting a needle stick injury in contrast to 53.7%. 19 All the respondents were using sterilized disposable syringe if needed which was indeed a very healthy practice.…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations